The effectiveness of village financial management in the implementation of accounting systems and procedures in Paloh District, Sambas Regency - Pudjianto, S.Y; Rasidar, Rasidar; Chainar, Chainar; Purnama, Desca; Marini, Marini (Research Horizon, 2023)
This research is based on the condition that the implementation of village financial management has not been maximized, which is reflected in poor financial administration and financial statements made not on time. The objectives of this study are 1. evaluate the effectiveness of the implementation of village financial management systems and procedures using the calculation of effectiveness ratio and efficiency ratio. 2. See what factors cause village financial management to not be optimal in Paloh District. The results showed that village financial management in eight villages in Paloh District was in accordance with the provisions of village financial management guidelines, and most villages reported that village budget realization could be said to be good because they were in the criteria of effective and efficient.